Hidden Narratives Dancers' Conceptualisations of Noncharacter Roles in Leotard Ballets by George Balanchine and William Forsythe - Tomic-Vajagic, Tamara (Edinburgh: Edinburgh University Press, 2016)
RESUMEN: The study of dancers' relationships with their noncharacter solo roles in leotard ballets by George Balanchine and Willian Forsythe reveals a dynamic cluster of flexible and multifaceted conceptualisations. Performers' process includes a range of abstract images, nonfictional and docufictional ideas, metaphoric allusions and storyboarding constructions. Drawing upon Michael Kirby's concept of non-matrixed performing (1987), as well as on ideas from dance aesthetics, narratology, theatre and film theories, noncharacter roles are understood as partly flexible, diverse performing frameworks that contain ambiguity but do not promote characterization. The findings suggest that the dissolution of character traits in plotless choreography often serves as a catalyst for the performers' polyvalent expressions of their artistic identities, value systems and agency. Observation of performances, in conjunction with direct interviews with expert dancers from several international ballet companies, brings to light the links between the performer's ideas and the effects observable in the dance. Attention to the performers' approaches and aspects of the work which they wish to emphasise reveals less observed aspects of dance text and illuminates the nature of the ballet dancer's qualitative contribution in non-narrative choreography. PALABRAS CLAVE: Dancer, Ballet, Noncharecter role, George Balanchine, William Forsythe, New York City Ballet, Frankfurt Ballet, The National Ballet of Canada, The Royal Ballet, Leotard ballet, Abstraction, Dancer's identity, Creative process, Dancer's agency, Non-narrative ballet, Dancer's interpretation, Docufiction